2002
DOI: 10.1021/la025631g
|View full text |Cite
|
Sign up to set email alerts
|

XAS and XPS Characterization of Monolayers Derived from a Dithiol and Structurally Related Disulfide-Containing Polyamides

Abstract: X-ray absorption spectroscopy and X-ray photoemission spectroscopy have been used to examine sulfur−gold bond formation in monolayers derived from a dithiol monomer and related disulfide-containing polyamides. These compounds were designed to allow the molecules to adsorb to gold through two terminal sulfurs, forming surface-attached loops. Element and site-specific density of unoccupied electronic states were probed by X-ray absorption spectroscopy at the C 1s, N 1s, O 1s (K-edge), and S 2p (L2,3-edge) absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
58
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 43 publications
17
58
1
Order By: Relevance
“…While the number of DTDTPA molecules per particle is in agreement with the values reported by Murray and co-workers [30] for gold particles coated by a monolayer of dodecanethiol molecules (monothiols), it appears to be too high to envisage the immobilization of these dithiolated ligands on gold nanoparticles by both sulfur atoms. The grafting of DTDTPA on the gold surface by only one thiol group is consistent with observations by Vance et al [31] They demonstrated that a,x-dithiol monomers are adsorbed onto gold preferentially by only one sulfur atom, whereas for the corresponding disulfide-containing polymer, after cleavage of the disulfide bonds, the monomer is grafted through both sulfur atoms, adopting a loop conformation.…”
Section: Full Papersupporting
confidence: 89%
“…While the number of DTDTPA molecules per particle is in agreement with the values reported by Murray and co-workers [30] for gold particles coated by a monolayer of dodecanethiol molecules (monothiols), it appears to be too high to envisage the immobilization of these dithiolated ligands on gold nanoparticles by both sulfur atoms. The grafting of DTDTPA on the gold surface by only one thiol group is consistent with observations by Vance et al [31] They demonstrated that a,x-dithiol monomers are adsorbed onto gold preferentially by only one sulfur atom, whereas for the corresponding disulfide-containing polymer, after cleavage of the disulfide bonds, the monomer is grafted through both sulfur atoms, adopting a loop conformation.…”
Section: Full Papersupporting
confidence: 89%
“…Each doublet results from spin-orbit splitting of the S 2p level and consists of a high-intensity S 2p3 = 2 peak at lower energy and a low-intensity S 2p1 = 2 peak at higher energy separated by 1.2 eV with an intensity ratio of 2:1. [58] The value of the S 2p3 = 2 peak at around 161.9 eV for monolayers of 14 and 15 is in excellent agreement with the binding energy for bound alkanethiolate on gold (161.9-162.0 eV). [53,59] Thus, peaks at 161.9 and 163.1 eV of the lower-energy doublet S 2p3 = 2 , 1 = 2 of [a] The corrected areas were calculated using empirically derived sensibility factors (C 1s: 0.3; S 2s: 0.4; S 2p: 0.57; Fe 2p: 2.7).…”
Section: Electrochemical and Optical Properties In Solutionsupporting
confidence: 66%
“…[58] www.chemeurj.org monolayers of 14 (161.9 and 163.0 eV for 15) may be assigned to the thiol chemisorbed on the Au surface. [58][59][60] The other doublet S 2p3 = 2 , 1 = 2 at 163.4 and 164.6 eV for 14 (163.6 and 164.8 eV for 15) corresponds to the other sulfur atoms of compound 14 (or 15).…”
Section: Electrochemical and Optical Properties In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…alkylmercaptanes [1b]) and cyclic disulfides showed to be efficient in the anchorage on gold of our spiro derivatives (other complex molecules as porphyrins [38] or catenanes [39] were successfully deposited on gold via cyclic disulfides). The degree of organization of the monolayers for our compounds is lower than in the case of the monolayers formed by the adsorbtion of more simple compounds (alkylmercaptanes [1b] or linear amides [40]). The relative flexible behavior of the absorbed spiro compounds determines a higher organization of the monolayers for our compounds than it was observed for the monoloyers obtained by the adsorbtion of the disulfides of rigid substrates (e.g.…”
Section: 13mentioning
confidence: 69%